Pengembangan Metode Market Place dalam Pembelajaran PAI - Ima Malihah; Mahlil Nurul Ihsan (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2020)
The purpose of this study is to describe the method of learning marktet place in PAI learning. This type of research uses a qualitative field research approach with descriptive analytical research methods. Data collection techniques are done by interview, observation and documentation..com The results of this study explain the PAI learning design using market place-oriented methods in the 2013 curriculum type of specific approach, the learning implementation consists of the planning, implementation and assessment stages, the evaluation of PAI learning using market place methods reaches 85% KKM, the supporting factors of this method are school leadership , support parents, teacher skills and support parents. While the inhibiting factors include differences in student characteristics, feelings of doubt, shame, require a long time and irrelevant student answers, the advantages of this method can increase participation, activeness, independence, student learning discipline and have a democratic attitude, the effectiveness of this method is achieved by good in learning PAI at SMPN 13 Bandung.Tujuan penelitian ini mendeskripsikan metode belajar marktet place dalam pembelajaran PAI. Jenis penelitian ini menggunakan pendekatan penelitian kualitatif lapangan dengan metode penelitian desktriptif analitis. Teknik pengumpulan data dilakukan dengan wawancara, observasi dan dokumentasi. Hasil penelitian ini menjelaskan desain pembelajaran PAI menggunakan metode market place berorientasi pada kurikulum 2013 berjenis pendakatan santifik, implementasi pembelajaran ini terdiri dari tahap perencanaan, pelaksanaan dan penilaian, evaluasi pembelajaran PAI menggunakan metode market place mencapai KKM 85%, faktor pendukung metode ini adalah kepemimpinan sekolah, dukungna orang tua, kemampuan guru dan dukungna orang tua. Sedangkan faktor penghambat di antaranya perbedaan karakteristik siswa, perasaan ragu, rasa malu, membetuhkan waktu yang panjang dan jawaban siswa yang tidak relevan, keunggulan metode ini dapat meningkatkan partisipasi, keaktifan, kemandirian, kedisiplinan belajar siswa dan memiliki sikap demokratis, keefektifan metode ini tercapai dengan baik di dalam pembelajaran PAI di SMPN 13 Bandung.